2020
DOI: 10.1038/s41467-020-18735-8
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc inactivation of p53 through the pan-cancer lncRNA MILIP drives cancer pathogenesis

Abstract: The functions of the proto-oncoprotein c-Myc and the tumor suppressor p53 in controlling cell survival and proliferation are inextricably linked as “Yin and Yang” partners in normal cells to maintain tissue homeostasis: c-Myc induces the expression of ARF tumor suppressor (p14ARF in human and p19ARF in mouse) that binds to and inhibits mouse double minute 2 homolog (MDM2) leading to p53 activation, whereas p53 suppresses c-Myc through a combination of mechanisms involving transcriptional inactivation and micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 69 publications
8
72
0
Order By: Relevance
“…Genomic ampli cation and transcriptional activation by E2F1 drive PLANE upregulation in diverse cancer types Through interrogating the lncRNA expression data in the Cancer Genome Atlas (TCGA) 29 , we identi ed a panel of eighteen pan-cancer upregulated lncRNAs that were increased in expression in at least 19 of 20 cancer types in relation to corresponding normal tissues ( Supplementary Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genomic ampli cation and transcriptional activation by E2F1 drive PLANE upregulation in diverse cancer types Through interrogating the lncRNA expression data in the Cancer Genome Atlas (TCGA) 29 , we identi ed a panel of eighteen pan-cancer upregulated lncRNAs that were increased in expression in at least 19 of 20 cancer types in relation to corresponding normal tissues ( Supplementary Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…One of the features of lncRNAs compared to protein-coding genes is their relatively poor sequence conservation 29,37 . By use of bioinformatics analysis, we identi ed a Gorilla transcript that is highly homologous to human PLANE with 92% sequence similarity (Supplementary Table 5), suggesting evolutionary conservation of PLANE between Hominidae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, the regulatory interactions are not retained by cancer cells as evidenced by the often-imbalanced expression of c-Myc over wildtype p53. 2 Although p53 repression is frequently associated with the loss of cyclin-dependent kinase inhibitor 2A (CDKN2A, best known as ARF) tumor suppressor (p14 ARF in human and p19 ARF in mouse), 3 Feng et al have recently reported an alternate mechanism whereby c-Myc inactivates p53 through the c-Myc-Inducible Long noncoding RNA (lncRNA) Inactivating P53 (MILIP) in the pancancer context, 4 uncovering an axis inhibiting p53 through a pan-cancer expressed lncRNA accomplice that links c-Myc to repression of p53.…”
mentioning
confidence: 99%
“…For the latter, c-Myc triggers activation of p53 through ARF, which serves as a key checkpoint to curb malignant transformation through induction of apoptosis. 5 Feng et al establish that c-Myc inactivates p53 through MILIP, 4 providing an explanation as to how wild-type p53 can be repressed by c-Myc independently of the loss of ARF. Noticeably, p14 ARF mRNA but not MILIP levels correlate with MYC gene expression in normal human tissues, 9 whereas Feng et al found that MILIP is upregulated and its expression is positively associated with the levels of MYC expression in human cancers.…”
mentioning
confidence: 99%